Organic Production Business Model and the Concept of Corporate Social Responsibility - ARABSKA, Ekaterina; TERZIEV, Venelin (Journal of Economic Development, Environment and People, 2016)
The concept of corporate social responsibility (CSR) considering competitiveness and sustainability issues in contemporary globalizing world is closely linked to organic production being a production system applying holistic approaches in the overall management and production activities and assurance of the highest degree of conformability to sustainable use and preservation of resources. The paper examines the organic production as a business model corresponding to the spheres of CSR regarding society, environment, human capital and work conditions, knowledge and education. The focus in on sustainable business practices in organic production assessed in the study from the point of view of management, environment, human resources, public relations and business environment considered in five dimensions: economic, social, environmental, cultural and accountability.